Irradiation effect of 780-805nm diode laser on wound healing in mice - Warkaa M Al-Wattar; Bashar H Abdulluh; Ali S Mahmmod (College of Dentistry/ University of Baghdad, 2014)
Background: Wound healing is a complicated, interactive, integrative process involving cellular and chemotactic activity, the release of chemical mediators and associated vascular response which includes number of phases: inflammatory phase, proliferative phase and remodeling phase. Low level laser therapy can be more effective in the three overlapping phases of wound healing. Biostimulation appears to have an effect on the cellular level, by increasing cellular function and stimulating various cells. The aim of present study was to evaluate histologically the effect of 780-805 diode laser the intensity of inflammation and pattern of epithelization in mice model. Material and methods: The experimental study was performed on ninety six white albino mice. An incision of 1.5cm length was done on the face side of each mouse. Then the animals were divided into two main groups; control group which didnt receive laser irradiation while the other group was the lased group which exposed to single dose of 360J/cm of 780-805nm diode laser. Animals were subdivided into four subgroups according to healing periods. Histological specimens were taken at 1st, 3rd, 7th and 14th day for microscopical examination concerning inflammatory cells infiltration and epithelial cell layer thickness. Results: Results show obvious reduction in inflammatory cell infiltration and more epithelization in laser treated wounds compared with control wounds. Statistical analysis showed a significant difference between two groups. Conclusion: Low level diode laser (790-805nm) has beneficial effects in enhancement of soft tissue wound healing process histologically.